2016
DOI: 10.1021/acs.jproteome.5b01125
|View full text |Cite
|
Sign up to set email alerts
|

Silencing PRDX3 Inhibits Growth and Promotes Invasion and Extracellular Matrix Degradation in Hepatocellular Carcinoma Cells

Abstract: PRDX3 is a mitochondrial peroxide reductase that regulates cellular redox state. It has been reported that PRDX3 is overexpressed in liver cancer, but how PRDX3 is involved in hepatocellular carcinoma (HCC) tumorigenesis and progression has not been well-characterized. In the present study, we established two stable cell lines by overexpressing or knocking down PRDX3 in HepG2 cells. We found that PRDX3 silencing decreased the growth rate of HepG2 cells and increased mtDNA oxidation. Quantitative proteomics ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…PRDX3 is the second most interconnected gene in CM2, was confirmed as upregulated with an independent hNP line and alternative shRNA to CLOCK (Supplemental Fig. S9), and has been shown to mediate cell migration in the HepG2 hepatocellular carcinoma cell line (Liu et al 2016). DISC1 is heavily implicated in both the schizophrenia and ASD disease pro-cess, and a mutant form of this gene has been linked to abnormal neocortical development due to migration defects (Kamiya et al 2005).…”
Section: Clock Expression Is Related To Coexpression Of Genes Involvementioning
confidence: 88%
“…PRDX3 is the second most interconnected gene in CM2, was confirmed as upregulated with an independent hNP line and alternative shRNA to CLOCK (Supplemental Fig. S9), and has been shown to mediate cell migration in the HepG2 hepatocellular carcinoma cell line (Liu et al 2016). DISC1 is heavily implicated in both the schizophrenia and ASD disease pro-cess, and a mutant form of this gene has been linked to abnormal neocortical development due to migration defects (Kamiya et al 2005).…”
Section: Clock Expression Is Related To Coexpression Of Genes Involvementioning
confidence: 88%
“…According to previous publications, high expression PRDX3 is associated with advanced malignant phenotype and worse prognosis in hepatocellular carcinoma [26], endometrial cancer [27], and medulloblastoma [28]. Besides, serum proteomics-based analysis identified autoantibodies against PRDX3 as potential diagnostic biomarkers in nasopharyngeal carcinoma [29].…”
Section: Discussionmentioning
confidence: 96%
“…Overexpression of PRDX3 has been implicated in several cancers, including prostate, breast, hepatocellular, colorectal, lung and nasopharyngeal cancer, suggesting that it supports increased metabolism and protects proliferating cancer cells from apoptosis and chemodestruction 21–28. Chang et al 29 identified PRDX3, via its effects on H 2 O 2 , to be a critical regulator of apoptotic signalling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these proteins are also involved in a range of other cellular roles, including the modulation of cytokine-induced hydrogen peroxide levels, which have been shown to mediate signalling cascades leading to gene expression, cell proliferation, differentiation and apoptosis 18–20. Overexpression of thioredoxin-dependent peroxidase reductase (PRDX3) has been implicated in several cancers, including prostate, breast, hepatocellular, colorectal, lung and nasopharyngeal cancer, suggesting that it supports increased metabolism and protects proliferating cancer cells from apoptosis and chemodestruction 21–28…”
Section: Introductionmentioning
confidence: 99%